Mapping of Mangrove Composition in Ratai Bay, Lampung Province using Pleiades 1 Satellite Imagery - Muhammad Sufwandika Wijaya; Muhammad Kamal; Prima Widayani (Universitas Pendidikan Indonesia, 2023)
Mangroves are vegetation with significant value in the coastal areas of Indonesia, protected through recognition as protected areas and national rehabilitation programs. In support of these efforts, information on mangrove composition distribution is crucial for biodiversity inventory in mangrove ecosystems. Remote sensing technology, such as Pleiades 1 satellite imagery, can map mangroves down to the family level. On the other hand, Teluk Ratai in Lampung has a well-established natural mangrove ecosystem within a protected area, but limited information is available regarding the composition of vegetation types within it. Therefore, this research aims to map the mangrove vegetation composition in Teluk Ratai using Pleiades 1 satellite imagery. The mapping method involves image segmentation and unsupervised classification to categorize the study area into vegetation classes for field surveys. The final vegetation composition classes are obtained through reclassification based on a key photo approach constructed from field data. The classification represents dominant lifeforms and species. The mapping results of mangrove composition in Teluk Ratai using Pleiades 1 satellite imagery reveal six mangrove composition classes with a total accuracy rate of 92%. The Forest class, dominated by Rhizophora apiculata species, is the largest, covering an area of 203.19 hectares out of the total mangrove area of 277.15 hectares in Teluk Ratai. Additionally, classes dominated by shrubs lifeforms, primarily composed of Rhizophora apiculata and Avicennia marina species, are frequently found in the mudflat areas at the mouth of the Ratai River.